Correction: Dynamic response study of Ti3C2-MXene films to shockwave and impact forces. Issue 12 (4th February 2021) - Srivatsa, Shreyas; Belthangadi, Pavithra; Ekambaram, Shivakarthik; Pai, Manu; Sen, Prosenjit; Uhl, Tadeusz; Kumar, Saurabh; Grabowski, Krzysztof; Nayak, M. M.
Abstract : Correction for 'Dynamic response study of Ti3 C2 -MXene films to shockwave and impact forces' by Shreyas Srivatsa et al., RSC Adv., 2020, 10, 29147–29155, DOI: ; 10.1039/D0RA04879H .